A preliminary soil security assessment of agricultural land in middle‐eastern China. (17th December 2018) - Yang, R.‐M.; Minasny, B.; Ma, Y.‐X.; Field, D.; McBratney, A.; Wu, C.‐F.
Abstract: Sustainable management of agricultural land requires not only an accurate assessment of the biophysical status of the soil but also estimates of the social and economic aspects of the soil. This paper focuses on soil security mapping of an approximately 80 000 km 2 agricultural area in middle‐eastern China. We examined a digital soil assessment framework in mapping soil security and its five dimensions (capability, condition, capital, connectivity and codification) using digital soil maps and environmental variables. The main objective is to improve the understanding of soil protection in agricultural practices. Soil and environmental variables were coded as indicator values based on their functions, and three averaging models were used to integrate the indicators for soil security mapping. Results show that agricultural land in the study area currently has a high potential to achieve the crop production function, while there is still lack of sufficient social connectivity. Most of agricultural land has been properly protected by the public policy. More than half of the agricultural land has high security for cropping, while there is no unsecured soil. In general, most of the agricultural lands have already been well developed for cropping. The low soil security mainly contributes to the lack of proper connection to the soil. The findings suggest that digital soil security assessment is highly recommended for guiding sustainable development of agricultural land, because it could provide the knowledge of factors affecting soil security from complex multifaceted dimensions, and potential solutions to make agriculture soil more secure.